A history of biogeographical regionalisation in Australia - Ebach, Malte C. (Zootaxa, 2012)
The development of Australian biogeographical regionalisation since 1858 has been driven by colonial 19th-centuryexploration and by the late 20th-century biodiversity crisis. The intervening years reduced existing large scaleregionalisation into smaller taxon specific areas of vegetation or endemism. However, large scale biotic biogeographicalregionalisation was rediscovered during multi-disciplinary meetings and conferences, sparking short-term revivals whichhave ended in constant revisions at smaller and smaller taxonomic scales. In 1995 and 1998, the Interim BiogeographicRegionalisation for Australia and the Integrated Marine and Coastal Regionalisation of Australia, AustralianCommonwealth funded initiatives in order to “identify appropriate regionalisations to assess and plan for the protectionof biological diversity”, have respectively replaced 140 years of Australian biogeographical regionalisation schemes. Thispaper looks at the rise and slow demise of biogeographical regionalisation in Australia in light of a fractured taxonomic biogeographical community.